(3CegGJ GdfHi Udi Gddg Ydjg hSdes - (3eMeO Hf MHjH Hf CejI Hf YeQh GdgGTej, HGdhdGA, CHh LYaQ GdHZOGOj, ef ehGdj Hfj GdYHGS,J (B245 (3g` s ((3GdMSf Hf Ydi Hf eMeO Hf GdMSjf Hf Ydi Hf CHj WGdH s)
(3ChdgG (B:s
(3CNHQfG CHh GdMSf GdSeQi bGd eMeO Udi Gddg Ydjg hSde hCeg BefI HfJ hgH Hf YHO efGa Hf RgQI Hf cdGH s
(3BNQgG (B:s
(3hgh gHI Gdgd Hf BOe Udi Gddg Ydjg hSde Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3QhGjI CHj GdMSf CMeO Hf eMeO Hf GdLge GdSeQi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B174s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs